The New Spedies of "Quinqueloculina" and "TRiloculina" from the bottom sea sediment of the Java Sea, Bali strait and Karimata Strait, Indonesia - Perpustakaan UGM, i-lib ([Yogyakarta] : Bagian Ilmu Penyakit Syaraf Fak. Kedokteran UGM, 1991)
ABSTRAK The bottoth sea samples were collected from Java Sea, Bali Strait and Karimata Strait. Those samples were identified systematically and discovered 3 new species of benthonic Foraminifera, i. e., Quinqueloculina aberensis n.sp., Triloculina malayensis n.sp., and Triloculina siuriensis n.sp. All of these species are included to the Family Miliolidae. Keywords: Bottom sea sediment